2012
DOI: 10.1085/jgp.201210851
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of hydrophobic residues in the pore-forming region of the ryanodine receptor channel to block by large tetraalkylammonium cations and Shaker B inactivation peptides

Abstract: Although no high-resolution structural information is available for the ryanodine receptor (RyR) channel pore-forming region (PFR), molecular modeling has revealed broad structural similarities between this region and the equivalent region of K+ channels. This study predicts that, as is the case in K+ channels, RyR has a cytosolic vestibule lined with predominantly hydrophobic residues of transmembrane helices (TM10). In K+ channels, this vestibule is the binding site for blocking tetraalkylammonium (TAA) cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…In KcsA channels, the inner α-helix equivalent to S6 undergoes a hinge-type movement that allows channel gating (28); it is therefore possible that substitution of RyR2-A4860 by the helix-breaker residue Gly may directly interfere with channel opening. In fact, experimental tests of the 3D model also indicate that mutations close to the A4860 residue and forming part of the same α-helix (I4867A, F4870A) profoundly affect channel gating (29). We found that the naturally occurring RyR2-A4860G mutation does not affect channel expression (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…In KcsA channels, the inner α-helix equivalent to S6 undergoes a hinge-type movement that allows channel gating (28); it is therefore possible that substitution of RyR2-A4860 by the helix-breaker residue Gly may directly interfere with channel opening. In fact, experimental tests of the 3D model also indicate that mutations close to the A4860 residue and forming part of the same α-helix (I4867A, F4870A) profoundly affect channel gating (29). We found that the naturally occurring RyR2-A4860G mutation does not affect channel expression (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…We have examined the influence of representative blockers of the full-length RyR2 on hRyR2-PFR. Tetrabutylammonium (TBA) and tetrapentylammonium (TPeA) are organic cations that interact with residues in the cytosolic vestibule of the full-length RyR2 channel [22]. When bound these molecules partially occlude the conduction pathway producing well-resolved blocking events with characteristic residual currents.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work from our group has established that a wide range of large monovalent and polyvalent cations are concentration‐ and voltage‐dependent blockers of cytosolic to luminal cation flux through the open RyR2 channel (Tinker et al ., 1992a, 1992b; Tinker and Williams, 1993; Mead and Williams, 2004; Mason et al ., 2012). Given this, it is logical to conclude that the open channel block reported here arises from the interaction of the cationic component of flecainide, QX‐FL and NU‐FL, with a site within the cytosolic vestibule of RyR2 channels.…”
Section: Discussionmentioning
confidence: 99%